Factors Affecting Attractive Mortgage – an Empirical Analysis - Karwowska, Milena (Journal of Finance and Financial Law, 2014)
The article presents characteristic crucial to a potential borrower, elements of the mortgage. The publication bring closer the importance of factors, such as creditworthiness, level of own contribution and security, loan interest rates, term of loan and currency. The article presents the results of research on a group of young people about their preferences of the perception of the mortgage and the influence of elements on the decisions of borrowers. Presented attitude of potential borrowers to a bank product which is mortgage.